Aminium-Radical-Mediated Intermolecular Hydroamination of Nonactivated Olefins - Jia, Si-Ming; Huang, Yi-Hang; Wang, Fei (Synlett, 2022)
Aminium radicals are attractive intermediates in synthetic chemistry that readily participate in a series of C–N bond-forming processes. Here, we briefly discuss strategies for generating aminium radicals from various precursors in the context of intermolecular alkene amination, and we highlight recent advances in aminium-radical-mediated hydroaminations of nonactivated olefins to directly approach alkylamines.1 Introduction2 Intermolecular Hydroamination of Nonactivated Alkenes with Alkylamines under Photoredox Catalysis3 Intermolecular Hydroamination of Nonactivated Alkenes with Aliphatic Azides4 Conclusions
Keywords: aminium radicals; hydroamination; alkenes; alkylamines; aliphatic azides